The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 2. Genus Protohyale Bousfield & Hendrycks, 2002 - Eun, Ye; Hendrycks, Ed A.; Kim, Young-Hyo (Zootaxa, 2016)
Five species of the genus Protohyale belonging to the family Hyalidae were collected from shallow coastal waters of Korea. Prior to our study, only two species, P. (Boreohyale) pumila (Hiwatari & Kajihara, 1981) and P. (B.) triangulata (Hiwatari, 2003) had been reported from Korea. One of the collected species, Protohyale (B.) magnaocularis is identified as a new species. The morphology of the eyes, antenna 1, gnathopod 2, uropods and telson are the major characteristics which differentiate P. (B.) magnaocularis sp. nov. from its congeners. The remaining two species, P. (B.) kajiharai (Hiwatari, 2003) and P. (B.) latimana (Hiwatari, 2003) are recorded for the first time from Korea. Protohyale (B.) kajiharai, P. (B.) latimana and P. (B.) magnaocularis sp. nov. are fully described and illustrated. A key to the species of Protohyale (B.) from Korea is also provided.